The Role and Place of Sign Language in Deaf Youth's Access to Literacy: Contributions of a Cross-Review of ASL-English and LSF-French Research - Beaujard, Laurence; Perini, Marie (Frontiers in Communication, 2022)
In this mini-review, we investigate the role sign language (SL) might play in the development of deaf learners’ reading skills. Since the recognition of American Sign Language (ASL) as a language in its own right thanks to the pioneering work of Stokoe (1960), SLs have been progressively included in research on reading development in the deaf, but with different statuses. Two contrasting paradigms can thus be identified in the literature. The first considers that sign language (SL) plays an indirect role in the development of reading skills. In line with the dominant psycholinguistic model of reading acquisition in hearing children, the authors consider that deaf children must first develop phonological representations in order to learn to read, like their hearing peers. For the authors of the second paradigm, SL plays a direct and central role in deaf children's access to reading as long as an appropriate visual (rather than phonological) mediation is made between the SL and the written language. We propose to present an overview of studies in both paradigms, in the English-language and French-language contexts. Then, we defend the idea of a "deaf norm", operating both in SL structuring and in information processing in general, justifying the central position that SL must have in any learning by deaf people. We will conclude by outlining some promising avenues for teaching reading to deaf learners.